Tendances actuelles de la recherche en ethno-biologie - Brunel, Gilles (Anthropologica, 2022)
This article discusses two orientations on ethnosemantics: ethnobiology and folk biology. In recent years, the folk biology approach has taken on importance and its methodology has become more and more sophisticated. It now presents relevant hypotheses with regard to the evolution of ethnosemantic categories and to the link between these categories and their socio-cultural milieu. The field of folk biology is thus developing an approach of its own which depends less and less on linguistic models.